PENGARUHPROFITABILITAS, STRUKTUR ASET, PERTUMBUHAN PERUSAHAAN, LIKUIDITAS, DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Alib Elyanti, 13.05.52.0149 (Students' Journal of Accounting and Banking, 2018)
This study aimed to analyze the effect of Profitability, Asset Structure, Growth, Liquidity and Business Risk on Capital Structure at Manufacturing Companies listed on the Indonesia Stock Exchange. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2013-2015. The sample selection was done by purposive sampling method with the number of observation data as much as 462. Data analysis usingmultiple linear regression.The results showed that profitability and liquidity have a negative and significant effect on capital structure. While the asset structure, growth and business risk do not affect the capital structure of the Manufacturing Company listed on the Indonesia Stock Exchange.Keywords: Profitability, Asset Structure, Growth, Liquidity, Business Risk and Capital Structure